Curettage and sclerotherapy technique: A hybrid approach to superficial lymphatic malformation. Issue 2 (29th November 2022) - Wang, Huaijie; Zhou, Jinbang; Lin, Weilong; Xie, Chong; Yang, Weijia; Guo, Zhengtuan
Abstract: Objective: To describe the curettage and sclerotherapy technique, a hybrid approach to treatment for superficial lymphatic malformations. Methods: A retrospective analysis of a lymphatic malformation data base was performed. Patients with superficial lymphatic malformation treated by curettage and sclerotherapy technique with bleomycin were included in this study. Safety and efficacy of the curettage and sclerotherapy technique with bleomycin were evaluated. Results: Between September 2019 and October 2021, 10 consecutive patients (male/female ratio: 4:6; mean age, 10.9 years; range, 3–35 years) presented with superficial lymphatic malformations that were subsequently treated by curettage and sclerotherapy technique with bleomycin. All lesions were located on the trunk and extremities. Each patient received one treatment session and a mean follow‐up of 12 months. We observed minor complications. No postoperative infections occurred in this series. No patient developed skin ulceration or necrosis. Scarring and recurrence occurred in one patient. Complete regression was confirmed for all 10 patients by photographic evaluation. Conclusion: A curettage and sclerotherapy technique is proposed to treat superficial lymphatic malformation in this study. This technique seems to be safe and highly effective.